2014
DOI: 10.1093/carcin/bgu114
|View full text |Cite
|
Sign up to set email alerts
|

Elevated HERV-K mRNA expression in PBMC is associated with a prostate cancer diagnosis particularly in older men and smokers

Abstract: Aberrant expression of subgroup k human endogenous retroviruses (HERV-K) has been observed in prostate cancer. This subgroup is unique because it encodes sequences in the human genome containing open reading frames for near intact retroviruses. We hypothesized that HERV-K reactivation could serve as a non-invasive early disease detection marker for prostate cancer. We evaluated HERV-K gag messenger RNA (mRNA) expression in blood samples of African-American and European-American men using a case-control design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 49 publications
2
84
0
Order By: Relevance
“…We have previously shown that ERV activity has been suppressed by body size throughout evolution, probably due to higher cancer burden [21], and so increased HERV expression could be detrimental. For example, increased HERV-K expression was detected in germ cell and trophoblastic tumours [17], melanoma cells [27], as well as in the blood of breast cancer [32] and prostate cancer patients [31]. However, whether the expression of HERVs drive tumorigenesis or are the result of the aberrant gene expression in cancers is still undetermined [11].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that ERV activity has been suppressed by body size throughout evolution, probably due to higher cancer burden [21], and so increased HERV expression could be detrimental. For example, increased HERV-K expression was detected in germ cell and trophoblastic tumours [17], melanoma cells [27], as well as in the blood of breast cancer [32] and prostate cancer patients [31]. However, whether the expression of HERVs drive tumorigenesis or are the result of the aberrant gene expression in cancers is still undetermined [11].…”
Section: Discussionmentioning
confidence: 99%
“…Serum proviral mRNA levels tended to be higher in the patients who later on developed the metastatic disease [207]. Aberrant overexpression of HERV-K/HML-2 (ERVK) proviruses was found also in prostate cancer [208] and HERV-K/HML-2 (ERVK) encoded transcripts or proteins are considered as possible biomarkers of malignization, being overexpressed for the patients with poor prognosis [209]. Increased HERV-K/ HML-2 (ERVK) Env gene expression was detected in the prostate tumors in 40 % of European-American and 61 % of African-American patients [208].…”
Section: Cancermentioning
confidence: 99%
“…Aberrant overexpression of HERV-K/HML-2 (ERVK) proviruses was found also in prostate cancer [208] and HERV-K/HML-2 (ERVK) encoded transcripts or proteins are considered as possible biomarkers of malignization, being overexpressed for the patients with poor prognosis [209]. Increased HERV-K/ HML-2 (ERVK) Env gene expression was detected in the prostate tumors in 40 % of European-American and 61 % of African-American patients [208]. Expression of some individual HERV-K/HML-2 (ERVK) elements can be of an outstanding importance to follow prostate cancer development, as recently shown for the HERV-K/HML-2 (ERVK) (ch22q11.23) Gag gene [209].…”
Section: Cancermentioning
confidence: 99%
“…[91][92][93][94][95][96][97] Nevertheless, characteristic patterns of HERVs expression are often seen in various tumors and can be considered as possible biomarkers of malignization, offering a unique approach to immunotherapy. 58 The major contribution of HERV sequences to the evolution of the species presumably depends on their LTRs that can trigger chromosomal breaks through recombination events and serve as natural or alternative promoters/enhancers, capable of modulating transcription.…”
Section: Hervs and Colon Cancermentioning
confidence: 99%